Arab Spring: Perubahan Otoritas, Stabilitas Politik dan Perkembangan Ekonomi di Timur Tengah - Effendi, Orien (Jurnal Review Politik, 2024)
This article examines the failure of the Arab Spring and the extent to which post-Arab Spring changes in authority have an impact on political and economic stability in the Middle East region such as Tunisia, Libya, Syria, Egypt and Yemen. The data in this research was collected from primary and secondary materials as well as field facts. Using a sociological-political and juridical-empirical approach, this article concludes that there are a number of factors in the failure of the Arab Spring, namely the unpreparedness of the Arab people in implementing a democratic system considering that they have used a monarchical system for centuries, there is domestic and regional polarization between countries in the Arab region. due to the pros and cons of the concept of democratization, and also the existence of foreign intervention. This article also finds evidence that changes in authority after the Arab Spring have actually had an impact on political and economic instability due to strengthening tribalism and competition between political elites in fighting for power after the fall of the previous regime. Apart from that, this research found another fact that the differences in economic conditions between countries in the Middle East region are not completely influenced by the chosen state system, although the democratization transition has also influenced political stability and then had an impact on the country's economic stability.